2022
DOI: 10.4314/dujopas.v7i4b.14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of post-harvest losses of banana and the economic wellbeing of farmers in Boyo Division, North West Region of Cameroon

Abstract: Post-harvest losses of banana affect the economic wellbeing of farmers in Africa especially in Boyo Division in the North West region of Cameroon where majority of the producers are smallholders’ farmers. The study analysed post-harvest losses of banana and its effect on the economic wellbeing of farmers in Boyo Division. Three hundred and eighty respondents were selected from three out of four sub-divisions in Boyo Division using a multi-stage sampling procedure. Data was obtained from the respondents with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These losses begin with site/seedlings/sucker selection and ends when harvesting begins. In a study on banana losses conducted in Cameroon by Nkwain [17], farmers insisted that pre-harvest losses pose a higher effect on their social wellbeing most especially food availability. Chief among their rationale was that strong wind, pest and diseases as well as fire devastate their crops living them with little or nothing to harvest and consume on daily, weekly and monthly bases hence, threaten their food security status.…”
Section: Pre-harvest Losses (Prhl)mentioning
confidence: 99%
See 4 more Smart Citations
“…These losses begin with site/seedlings/sucker selection and ends when harvesting begins. In a study on banana losses conducted in Cameroon by Nkwain [17], farmers insisted that pre-harvest losses pose a higher effect on their social wellbeing most especially food availability. Chief among their rationale was that strong wind, pest and diseases as well as fire devastate their crops living them with little or nothing to harvest and consume on daily, weekly and monthly bases hence, threaten their food security status.…”
Section: Pre-harvest Losses (Prhl)mentioning
confidence: 99%
“…Reports showed that Fusarium wilt, a disease that is predominant in Gros Michel banana varieties affect banana plants in Cameroon, Nigeria, Rwanda and Burundi causing the dryingoff of the leaves starting from the older ones to the shoot and eventually the whole plant [17,34]. Once a plant is affected with this disease, the leaves turn yellow and collapses.…”
Section: Diseasesmentioning
confidence: 99%
See 3 more Smart Citations